Sexual risk behaviors in Brazilian adolescents and young women: a community-based study - Anjos, Caroline Ferreira dos; Alves, Rosane Ribeiro Figueiredo; Alves, Maria de Fátima Costa; Santos, Silvia Helena Rabelo (Brazilian Journal of Sexually Transmitted Diseases, 2018)
Introduction: Risky sexual behaviors among adolescents can result in high rates of sexually transmitted infections and unwanted pregnancies. Objective: To estimate the prevalence and to identify sociodemographic factors associated with early start of sexual activity and inconsistent condom use among adolescents and young women. Methods: This cross-sectional, community-based study enrolled 1,072 women from 2007 to 2009. The participants were between 15 and 24 years old and were residents of three different mid-sized cities in the state of Goiás, Central-Western region of Brazil. Sociodemographic and behavioral data were collected in a structured questionnaire, following ethics committee approval. Logistic regression analysis was performed, with odds ratio and adjusted odds ratio calculation, with confidence interval of 95% (95%CI) and statistical significance of 5% (p<0.05). Results: Of the 1,072 interviewees, 64.9% were sexually active, of which 46.4% reported sexual initiation at the age of 15 or younger, and 73.2% reported inconsistent condom use. The factors associated with the early start of sexual activity were to be under 20, to have less than eight years of education, and to report no religion with odds ratio of 3.13 (95%CI 2.22–4.40), 6.21 (95%CI 4.41–9.32) and 2.05 (95%CI 1.17–3.58) respectively. The factor associated with inconsistent condom use was being married or in a stable relationship, with odds ratio of 4.63 (95%CI 2.86–7.50). Conclusion: The high prevalence of risky sexual behaviors among Brazilian adolescents and young women is due to socioeconomic and cultural factors.